Thermal transfer carbon ribbon back coating material and preparation method thereof and back coating liquid for thermal transfer carbon ribbon
Through copolymerization technology, silicone modified polyurethane-acrylate copolymer emulsion was prepared, which solved the defects of the existing thermal transfer carbon tape backcoat materials in terms of heat resistance, smoothness and adhesive properties, and achieved a more efficient print head service life and more stable print quality.
Patent Information
- Application Number
- CN202411614206.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing thermal transfer carbon tape backcoat materials have defects in heat resistance, smoothness and adhesive properties, resulting in a shortened life of the print head and unstable print quality.
By combining polyurethane, acrylate and silicone by copolymerization technology, silicone modified polyurethane-acrylate copolymer emulsion was prepared for the preparation of thermal transfer carbon tape back coating material. This method performs stirring and reflux reaction under catalyst conditions to ensure excellent heat resistance, smoothness and adhesive properties of the material.
The thermal transfer carbon tape back coating material has achieved significant improvements in heat resistance, smoothness and adhesive properties, extending the service life of the print head and improving the stability of the print quality.
Smart Images

Figure CN119119387B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing materials, in particular to a thermal transfer carbon ribbon back coating material and a preparation method thereof, and a back coating liquid for the thermal transfer carbon ribbon. Background Art
[0002] The ribbon back coating is where the ribbon comes into direct contact with the printer's print head. Its function is to protect the print head as the ribbon is unwound (from the wound state) and to provide excellent heat transfer so that ink can be transferred to the media, reducing the formation of static electricity that is harmful to the printer and printer operators, thereby extending the life of the print head.
[0003] Because the carbon ribbon needs to bear the high temperature generated instantly by the thermal print head during the thermal transfer process, a back coating needs to be applied on one side of the substrate. The back coating not only needs to have high heat resistance, but also needs to have good smoothness to ensure a smooth transfer process. More importantly, the back coating must have excellent adhesion to the substrate to ensure that the glue does not fall off during a long transfer process, avoiding contamination of the print head.
[0004] The field of thermal transfer ribbon back coating mainly involves silicone modified acrylate back coating and silicone modified polyurethane back coating, both of which have their own advantages and disadvantages. Silicone modified acrylate back coating materials have good heat resistance but poor adhesion to the substrate, which can easily cause print head contamination and reduce the service life of the print head. Silicone modified polyurethane back coating materials have good adhesion to the substrate but poor heat resistance. The ribbon is prone to sticky film when placed in a high temperature environment for a long time, and high-energy level printing ribbons are prone to breakdown. It can be seen that both existing back coating materials have certain defects.
[0005] Therefore, it is necessary and urgent to research and develop a thermal transfer carbon ribbon back coating material that has heat resistance, good slippery performance, strong stability and excellent bonding performance.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a method for preparing a thermal transfer carbon ribbon back coating material, wherein the preparation method is to combine polyurethane, acrylate and silicone through copolymerization to obtain a silicone-modified polyurethane-acrylate copolymer. The thermal transfer carbon ribbon back coating material has excellent technical effects in properties such as heat resistance, smoothness and adhesion, and effectively alleviates the defects of existing silicone-modified acrylate back coatings and silicone-modified polyurethane back coatings.
[0008] The second object of the present invention is to provide a thermal transfer carbon ribbon back coating material.
[0009] The third object of the present invention is to provide a back coating liquid for a thermal transfer carbon ribbon.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention provides a method for preparing a thermal transfer carbon ribbon back coating material, wherein the material is an organosilicon-modified polyurethane-acrylate copolymer emulsion;
[0012] The preparation method comprises:
[0013] (A) Under the condition of a catalyst, toluene diisocyanate (TDI-100) and polytetramethylene glycol (PTMG) are stirred and refluxed to obtain a polyurethane prepolymer;
[0014] (B) adding hydroxy-terminated polydimethylsiloxane (HO-PDMS-OH) dropwise to the polyurethane prepolymer for stirring and reflux reaction to obtain a silicone-modified polyurethane prepolymer, and then adding hydroxyethyl methacrylate (HEMA) for end-capping to obtain a carbon-carbon double bond-end-capped silicone-modified polyurethane prepolymer;
[0015] (C) Adding an acrylate monomer and an initiator to a carbon-carbon double bond terminated organosilicon-modified polyurethane prepolymer to carry out a stirring reflux reaction to obtain an organosilicon-modified polyurethane-acrylate copolymer emulsion.
[0016] Furthermore, in step (A), the catalyst is one of dibutyltin dilaurate or stannous octoate;
[0017] Furthermore, in the step (C), the initiator is one of benzoyl peroxide and azobisisobutyronitrile.
[0018] Furthermore, the polytetrahydrofuran ether diol in step (A) is polytetrahydrofuran ether diol after vacuum drying and dehydration, and the temperature of vacuum drying and dehydration is 110° C.;
[0019] And / or, the terminal hydroxyl polydimethylsiloxane in the step (B) is the terminal hydroxyl polydimethylsiloxane after vacuum drying and dehydration, and the temperature of the vacuum drying and dehydration is 110°C.
[0020] Furthermore, in step (C), the acrylic ester monomers include methyl methacrylate (MMA) and butyl acrylate (BA).
[0021] Further, the following monomers are included based on the total monomer percentage of the organic silicon modified polyurethane-acrylate copolymer: 20-25% of polytetramethylene ether glycol, 10-16% of toluene diisocyanate, 14-25% of terminal hydroxyl polydimethylsiloxane, 3-6% of hydroxyethyl methacrylate, 35-40% of methyl methacrylate, and 3-7% of butyl acrylate;
[0022] Preferably, the following monomers are included, based on the percentage of the total amount of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer: 21% polytetramethylene ether glycol, 12% toluene diisocyanate, 20% terminal hydroxyl polydimethylsiloxane, 5% hydroxyethyl methacrylate, 38% methyl methacrylate, and 4% butyl acrylate.
[0023] Furthermore, in step (A), the temperature of the stirring reflux reaction is 70-80° C., and the time of the stirring reflux reaction is 2-4 hours;
[0024] Preferably, the stirring reflux reaction in step (A) is carried out under an inert atmosphere.
[0025] Furthermore, in the step (B), the temperature of the stirring reflux reaction is 70-80° C., and the time of the stirring reflux reaction is 2-4 hours.
[0026] Preferably, the stirring reflux reaction in step (B) is carried out under an inert atmosphere.
[0027] Furthermore, the end-capping reaction in step (B) is carried out under stirring and reflux conditions, the stirring and reflux temperature is 70-80° C., and the stirring and reflux reaction time is 1-3 hours. Preferably, the stirring and reflux reaction in the above end-capping process is carried out under an inert atmosphere.
[0028] Furthermore, in the step (C), the temperature of the stirring reflux reaction is 70-80° C., and the time of the stirring reflux reaction is 3-5 h.
[0029] Preferably, the stirring reflux reaction in step (C) is carried out under an inert atmosphere.
[0030] Furthermore, the amount of the catalyst added in step (A) is 0.08-0.13% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer;
[0031] Furthermore, the amount of the initiator added in step (C) is 0.3-0.6% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer.
[0032] The present invention provides a thermal transfer carbon ribbon back coating material, which is mainly prepared by the thermal transfer carbon ribbon back coating material preparation method mentioned above.
[0033] The present invention provides a back coating liquid for a thermal transfer carbon ribbon, wherein the back coating liquid is mainly obtained by diluting the above-mentioned thermal transfer carbon ribbon back coating material with a solvent;
[0034] The solvent is a mixed solvent, and the mixed solvent includes at least two of toluene, butanone and methanol.
[0035] Furthermore, the content of the thermal transfer carbon ribbon back coating material in the back coating liquid is 15-25wt%, preferably 20wt%.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention provides a method for preparing a thermal transfer carbon ribbon back coating material. The method firstly synthesizes a silicone-modified polyurethane prepolymer containing carbon-carbon double bonds by solution copolymerization, and then introduces an acrylate molecular chain therein by free radical polymerization, thereby obtaining a silicone-modified polyurethane-acrylate copolymer suitable for a thermal transfer carbon ribbon back coating. The present application combines polyurethane-acrylate-organosilicon by the above method, effectively alleviating the defects of silicone-modified acrylate back coating and silicone-modified polyurethane back coating. The thermal transfer carbon ribbon back coating material prepared by the present application has excellent technical effects in terms of heat resistance, smoothness, adhesion and other properties.
[0038] The thermal transfer carbon ribbon back coating material provided by the present invention is mainly prepared by the above-mentioned preparation method of the thermal transfer carbon ribbon back coating material. The thermal transfer carbon ribbon back coating material has excellent heat resistance, smoothness and bonding performance.
[0039] The back coating liquid for the thermal transfer carbon ribbon provided by the present invention is mainly obtained by diluting the thermal transfer carbon ribbon back coating material with a solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 This is a reaction process diagram for the preparation of the silicone-modified polyurethane-acrylate copolymer emulsion provided in this application. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] According to one aspect of the present invention, a method for preparing a thermal transfer carbon ribbon back coating material, wherein the material is an organosilicon-modified polyurethane-acrylate copolymer emulsion;
[0044] Figure 1 This is a reaction process diagram for the preparation of the silicone-modified polyurethane-acrylate copolymer emulsion provided in this application.
[0045] See also Figure 1 , the preparation method of the silicone-modified polyurethane-acrylate copolymer emulsion comprises:
[0046] (A) in the presence of a catalyst, stirring and refluxing toluene diisocyanate and polytetramethylene ether diol to obtain a polyurethane prepolymer;
[0047] (B) adding hydroxy-terminated polydimethylsiloxane dropwise to the polyurethane prepolymer for stirring and reflux reaction to obtain an organosilicon-modified polyurethane prepolymer, and then adding hydroxyethyl methacrylate for end-capping to obtain an organosilicon-modified polyurethane prepolymer end-capped with a carbon-carbon double bond;
[0048] (C) Adding an acrylate monomer and an initiator to a carbon-carbon double bond terminated organosilicon-modified polyurethane prepolymer to carry out a stirring reflux reaction to obtain an organosilicon-modified polyurethane-acrylate copolymer emulsion.
[0049] The present invention provides a method for preparing a thermal transfer carbon ribbon back coating material. The method firstly synthesizes a silicone-modified polyurethane prepolymer containing carbon-carbon double bonds by solution copolymerization, and then introduces an acrylate molecular chain therein by free radical polymerization, thereby obtaining a silicone-modified polyurethane-acrylate copolymer suitable for a thermal transfer carbon ribbon back coating. The present application combines polyurethane-acrylate-organosilicon by the above method, effectively alleviating the defects of silicone-modified acrylate back coating and silicone-modified polyurethane back coating. The thermal transfer carbon ribbon back coating material prepared by the present application has excellent technical effects in terms of heat resistance, smoothness, adhesion and other properties.
[0050] In a preferred embodiment of the present invention, the catalyst in step (A) is one of dibutyltin dilaurate or stannous octoate;
[0051] In a preferred embodiment of the present invention, the initiator in step (C) is one of benzoyl peroxide and azobisisobutyronitrile.
[0052] In a preferred embodiment of the present invention, the polytetrahydrofuran ether diol in the step (A) is polytetrahydrofuran ether diol after vacuum drying and dehydration, and the temperature of the vacuum drying and dehydration is 110°C;
[0053] As a preferred embodiment, the polytetrahydrofuran ether diol after vacuum drying and dehydration can effectively prevent the side reaction between water and isocyanate groups, which would cause the performance of the product to decrease.
[0054] In a preferred embodiment of the present invention, the hydroxy-terminated polydimethylsiloxane in step (B) is hydroxy-terminated polydimethylsiloxane that has been vacuum dried and dehydrated, and the temperature of the vacuum drying and dehydration is 110°C.
[0055] In a preferred embodiment of the present invention, the acrylic ester monomers in step (C) include methyl methacrylate and butyl acrylate.
[0056] As a preferred embodiment, the acrylic acid ester monomers of the present application include methyl methacrylate and butyl acrylate, and the Tg of the synthetic polymer is regulated by adjusting the ratio of MMA and BA (the ratio of the soft and hard segments of the acrylic acid ester monomers), thereby ensuring that the carbon ribbon does not stick to the film at a higher temperature after being wound.
[0057] In a preferred embodiment of the present invention, the total amount of monomers used to prepare the organosilicon-modified polyurethane-acrylate copolymer includes the following monomers: 20-25% polytetramethylene glycol, 10-16% toluene diisocyanate, 14-25% terminal hydroxyl polydimethylsiloxane, 3-6% hydroxyethyl methacrylate, 35-40% methyl methacrylate, and 3-7% butyl acrylate;
[0058] Typical but non-limiting preferred embodiments of the above-mentioned polytetramethylene ether diol are: 20%, 21%, 22%, 23%, 24% and 25%; typical but non-limiting preferred embodiments of the above-mentioned toluene diisocyanate are: 10%, 11%, 12%, 13%, 14%, 15% and 16%; typical but non-limiting preferred embodiments of the above-mentioned terminal hydroxy polydimethylsiloxane are: 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% and 25%; typical but non-limiting preferred embodiments of the above-mentioned hydroxyethyl methacrylate are: 3%, 4%, 5% and 6%; typical but non-limiting preferred embodiments of the above-mentioned methyl methacrylate are: 35%, 36%, 37%, 38%, 39% and 40%; typical but non-limiting preferred embodiments of the above-mentioned butyl acrylate are: 3%, 4%, 5%, 6% and 7%.
[0059] Preferably, the following monomers are included, based on the percentage of the total amount of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer: 21% polytetramethylene ether glycol, 12% toluene diisocyanate, 20% terminal hydroxyl polydimethylsiloxane, 5% hydroxyethyl methacrylate, 38% methyl methacrylate, and 4% butyl acrylate.
[0060] As a preferred embodiment, the thermal transfer carbon ribbon back coating material of the present application is mainly prepared by polytetramethylene ether glycol, toluene diisocyanate, terminal hydroxyl polydimethylsiloxane, hydroxyethyl methacrylate, methyl methacrylate, butyl acrylate, a catalyst and an initiator in a specific ratio. It has been verified by experiments that the selection of the component content of the above raw materials of the present application has a significant effect on the performance of the thermal transfer carbon ribbon back coating material finally prepared.
[0061] Specific:
[0062] 1. The present application uses the above-mentioned content range of hydroxy-terminated polydimethylsiloxane (HO-PDMS-OH) to regulate the heat resistance and smoothness of the synthesized back coating material. The technical solution that is not within the above-mentioned HO-PDMS-OH content range of the present application has poor heat resistance and smoothness of the prepared back coating material;
[0063] 2. The present application uses the catalyst DBTDL in the above-mentioned content range to regulate the molecular weight of the carbon-carbon double bond terminated silicone-modified polyurethane prepolymer. Control of the molecular weight of the carbon-carbon double bond terminated silicone-modified polyurethane prepolymer is the key to the excellent heat resistance, smoothness and adhesion of the thermal transfer carbon tape back coating material of the present invention.
[0064] If the molecular weight of the organosilicon-modified polyurethane prepolymer is too low, when the acrylic ester monomers (MMA and BA) are added for free radical polymerization, the reaction will be violent, gelation will occur easily, and it will be difficult to control; while if the molecular weight of the organosilicon-modified polyurethane prepolymer is too high, the reaction rate will be slow and the reaction time will be long. It has been verified that in the implementation method within the above DBTDL content range (0.08-0.13%) of the present application, the molecular weight of the organosilicon-modified polyurethane terminated with carbon-carbon double bonds can be controlled within 8000~10500 / g.mol-1. Within this molecular weight range, the emulsion stability is good after free radical polymerization with the addition of acrylic ester monomers, and the reaction process is stable.
[0065] 3. The present application adjusts the Tg of the synthetic polymer by adjusting the ratio of the soft and hard segments of the acrylic ester monomers within the above content range (i.e., the ratio of MMA and BA), so as to ensure that the carbon ribbon does not stick to the film at a higher temperature after winding;
[0066] 4. The present application controls the molecular weight of the synthetic polymer by using the initiator in the above content range, thereby regulating the brittleness and toughness of the synthetic back coating, thereby improving the bonding performance between the back coating agent and the substrate film.
[0067] In a preferred embodiment of the present invention, the stirring reflux reaction temperature in step (A) is 70-80° C., and the stirring reflux reaction time is 2-4 h;
[0068] In a preferred embodiment of the present invention, the stirring reflux reaction temperature in step (B) is 70-80° C., and the stirring reflux reaction time is 2-4 h.
[0069] In a preferred embodiment of the present invention, the end-capping reaction in step (B) is carried out under stirring and reflux conditions, the stirring and reflux temperature is 70-80° C., and the stirring and reflux reaction time is 1-3 h.
[0070] In a preferred embodiment of the present invention, the stirring reflux reaction temperature in step (C) is 70-80° C., and the stirring reflux reaction time is 3-5 h.
[0071] It should be noted that the preparation process of the thermal transfer carbon ribbon back coating material of the present application is carried out under stirring and reflux conditions. Within the stirring and reflux parameter range of the above steps (A) to (C), the preparation method of the present application has the advantages of stable, complete and rapid reaction.
[0072] At the same time, it should be noted that the stirring reflux reactions in the above steps (A) to (C) of the present application are all carried out under an inert atmosphere. Under the protection of the above inert atmosphere, not only can the reactants in the preparation process of the present application be effectively prevented from being oxidized by oxygen in the air, but also the reactants can be prevented from reacting with moisture in the air.
[0073] In a preferred embodiment of the present invention, the amount of the catalyst added in step (A) is 0.08-0.13% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer;
[0074] Typical but non-limiting preferred embodiments of the above catalyst are: 0.08%, 0.09%, 0.1%, 0.11%, 0.12% and 0.13%;
[0075] In a preferred embodiment of the present invention, the amount of the initiator added in step (C) is 0.3-0.6% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer.
[0076] Typical but non-limiting preferred embodiments of the above initiators are: 0.3%, 0.4%, 0.5% and 0.6%.
[0077] Preferably, the method for preparing the thermal transfer carbon ribbon back coating material comprises:
[0078] (1) In a 500 ml four-necked flask equipped with a polytetrafluoroethylene stirring blade, a thermometer, a constant pressure dropping funnel, and a condenser, 20%-25% of polytetrahydrofuran ether glycol (PTMG), 10%-16% of TDI-100, 0.08-0.13% of a catalyst dibutyltin dilaurate (DBTDL), and a mixed solvent of butanone and toluene in a mass ratio of 1:1 were added respectively, and then the temperature was raised to 70-80°C under an inert atmosphere, and the mixture was stirred and refluxed for 2-4 hours to obtain a polyurethane prepolymer;
[0079] The polytetrahydrofuran ether diol is polytetrahydrofuran ether diol that has been vacuum dried and dehydrated at 110° C.;
[0080] (2) Add 14%-25% of hydroxy-terminated polydimethylsiloxane (HO-PDMS-OH) to the polyurethane prepolymer, at 70-80°C, continue stirring and reflux reaction for 2-4 hours to obtain a silicone-modified polyurethane prepolymer;
[0081] The terminal hydroxyl polydimethylsiloxane is the terminal hydroxyl polydimethylsiloxane that has been vacuum dried and dehydrated at 110°C;
[0082] (3) The isocyanate group content in the organosilicon-modified polyurethane prepolymer system was monitored by the di-n-butylamine method. When the isocyanate group content reached 3-7%, 3-6% HEMA was added dropwise and the mixture was stirred and refluxed at 70-80°C for 1-3 hours for end-capping reaction until the isocyanate group reaction was completed to obtain an organosilicon-modified polyurethane prepolymer end-capped with a carbon-carbon double bond.
[0083] (4) Cool the carbon-carbon double bond terminated silicone-modified polyurethane prepolymer to 40°C, add 35-40% methyl methacrylate (MMA) and 3-7% butyl acrylate (BA), raise the temperature to 70-80°C, add 0.3-0.6% initiator (BPO), stir and reflux for 3-5 hours to obtain silicone-modified polyurethane-acrylate copolymer emulsion.
[0084] According to one aspect of the present invention, a thermal transfer carbon ribbon back coating material is provided. The thermal transfer carbon ribbon back coating material is mainly prepared by the above-mentioned method for preparing the thermal transfer carbon ribbon back coating material.
[0085] The thermal transfer carbon ribbon back coating material provided by the present invention is mainly prepared by the above-mentioned preparation method of the thermal transfer carbon ribbon back coating material. The thermal transfer carbon ribbon back coating material has excellent heat resistance, smoothness and bonding performance.
[0086] According to one aspect of the present invention, a back coating liquid for a thermal transfer carbon ribbon is provided, wherein the back coating liquid is mainly obtained by diluting the above-mentioned thermal transfer carbon ribbon back coating material with a solvent;
[0087] The solvent is a mixed solvent, and the mixed solvent includes at least two of toluene, butanone and methanol.
[0088] In a preferred embodiment of the present invention, the content of the thermal transfer carbon ribbon back coating material in the back coating liquid is 20wt%.
[0089] The technical solution of the present invention will be further described below in conjunction with embodiments.
[0090] Note: The materials, equipment and reagents required in the following examples include and are selected as follows:
[0091] Constant temperature water bath, 500ml four-necked flask, thermometer, constant pressure dropping funnel, condenser, polytetrafluoroethylene stirring paddle, butanone, toluene, cyclohexanone, methanol, methyl methacrylate (MMA), butyl acrylate (BA), benzoyl peroxide (BPO), polytetramethylene glycol (PTMG, Mn=2000 g / mol), hydroxy-terminated polydimethylsiloxane (HO-PDMS-OH, Mn=1800g / mol), TDI-100, hydroxyethyl methacrylate (HEMA), dibutyltin dilaurate (DBTDL).
[0092] Example 1
[0093] A method for preparing a thermal transfer carbon ribbon back coating material, wherein the material is an organosilicon-modified polyurethane-acrylate copolymer emulsion;
[0094] The following monomers are included, based on the total monomer percentage for preparing the organosilicon-modified polyurethane-acrylate copolymer: 21% of polytetramethylene ether glycol, 12% of toluene diisocyanate, 20% of terminal hydroxyl polydimethylsiloxane, 5% of hydroxyethyl methacrylate, 38% of methyl methacrylate, and 4% of butyl acrylate.
[0095] The preparation method of the thermal transfer carbon ribbon back coating material comprises:
[0096] (1) In a 500 ml four-necked flask equipped with a polytetrafluoroethylene stirring blade, a thermometer, a constant pressure dropping funnel, and a condenser, polytetrahydrofuran ether glycol, TDI-100, a catalyst dibutyltin dilaurate, and a mixed solvent of butanone and toluene in a mass ratio of 1:1 were added respectively, and then the temperature was raised to 75° C. under an inert atmosphere, and stirred and refluxed for 3 hours to obtain a polyurethane prepolymer;
[0097] The polytetrahydrofuran ether diol is polytetrahydrofuran ether diol that has been vacuum dried and dehydrated at 110° C.;
[0098] The catalyst dibutyltin dilaurate is added in an amount of 0.1% of the total mass of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer;
[0099] (2) Add terminal hydroxyl polydimethylsiloxane dropwise to the polyurethane prepolymer, and continue stirring and refluxing at 75°C for 3 hours to obtain a silicone-modified polyurethane prepolymer;
[0100] The terminal hydroxyl polydimethylsiloxane is the terminal hydroxyl polydimethylsiloxane that has been vacuum dried and dehydrated at 110°C;
[0101] (3) The isocyanate group content in the organosilicon-modified polyurethane prepolymer system was monitored by the di-n-butylamine method. When the isocyanate group content reached 3-7%, hydroxyethyl methacrylate was added dropwise and the mixture was stirred and refluxed at 75°C for 2 h for a capping reaction until the isocyanate group reaction was completed to obtain a carbon-carbon double bond-capped organosilicon-modified polyurethane prepolymer.
[0102] (4) Cool the carbon-carbon double bond terminated silicone-modified polyurethane prepolymer to 40°C, add methyl methacrylate and butyl acrylate, raise the temperature to 75°C, add initiator BPO, stir and reflux for 4 hours, and obtain silicone-modified polyurethane-acrylate copolymer emulsion.
[0103] The amount of the initiator added is 0.5% of the total weight of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer.
[0104] Furthermore, the organosilicon-modified polyurethane-acrylate copolymer emulsion obtained in step (4) is cooled to room temperature (20-25° C.), and then a mixed solvent of toluene, butanone and methanol (toluene: methanol: butanone = 6:3:1) is added to dilute the organosilicon-modified polyurethane-acrylate copolymer emulsion to 20%, thereby obtaining an organosilicon-modified polyurethane-acrylate back coating liquid for a thermal transfer ribbon.
[0105] Application Example 1
[0106] The coating amount of the organosilicon-modified polyurethane-acrylate back coating liquid prepared in Example 1 above was tested.
[0107] Specific:
[0108] A mixed solvent of butanone and toluene in a mass ratio of 7:3 was added to the 20% organosilicon-modified polyurethane-acrylate back coating liquid prepared in Example 1 above, and the mixture was diluted to concentrations of 2%, 3%, 3.5%, 4%, 4.5% and 5%, respectively; then, back coating was performed on one side of the base film and the coating amount at each mass fraction was measured, and a primer layer and an ink layer were applied on the other side. After drying in an oven, complete carbon ribbons (corresponding to carbon ribbons 1 to 6 in the table below) were obtained respectively; and then the performance of the carbon ribbons was tested.
[0109] The test results are as follows:
[0110]
[0111] Note: The breakdown performance shown in the table above refers to the highest energy level that the ribbon can withstand. The "2" in 2 / 18 refers to the printing speed of the printer, and "18" refers to the printing energy level of the printer. 2 / 18 means that the ribbon breaks down when the printing speed is 2 and the energy level is 18. The printing noise is measured by a decibel meter after printing 10 sheets continuously on the media used. The print head contamination is measured by printing 20,000 sheets continuously on PET label paper to observe whether the print head is contaminated, which directly reflects the smoothness and bonding performance of the coating material.
[0112] As can be seen from the table above, the concentration of the back coating liquid in this application needs to be controlled within the range of 3-4%, thereby keeping the coating amount at 0.1-0.15 g / m 2 , in order to maintain the best performance of the back coating and ensure smooth transfer process during printing. When the back coating amount is high, white residue will appear on the print head during continuous printing, causing damage to the print head; and when the back coating amount is low, the instantaneous high temperature generated by the print head will break through the carbon ribbon and affect the continuity of printing.
[0113] Embodiment 2~6
[0114] Except that the contents of the raw materials for preparing the back coating material of the thermal transfer carbon ribbon are different from those in Example 1, the rest of Examples 2 to 6 are the same as those in Example 1.
[0115]
[0116] Test Example 1
[0117] Effect of the content of hydroxyl-terminated polydimethylsiloxane (HO-PDMS-OH) on the heat resistance and smoothness of silicone-modified polyurethane-acrylate coating materials. The back coating liquids prepared in Examples 1 to 6 were prepared into thermal transfer carbon ribbons for performance testing.
[0118] Note: The thermal transfer carbon ribbon in this test example was prepared by referring to the preparation method of carbon ribbon 3 in application example 1 (back coating liquid concentration is 3.5%), that is, except for the selected silicone modified polyurethane-acrylate back coating liquid, the rest of the preparation method is the same as carbon ribbon 3 in application example 1.
[0119] The specific detection methods are as follows:
[0120] Heat resistance is characterized by thermal decomposition temperature. The higher the thermal decomposition temperature, the better the heat resistance. In addition, the heat resistance can be judged by the breakdown energy level during the printing process. Generally, the higher the breakdown energy level, the better the heat resistance. The smoothness of the material can be characterized by the dynamic friction coefficient. The lower the dynamic friction coefficient, the better the smoothness.
[0121] The specific test results are as follows:
[0122]
[0123] As can be seen from the table above, the thermal decomposition temperature of the coating material increases first and then decreases with the increase of the content of terminal hydroxyl polydimethylsiloxane. When the content of terminal hydroxyl polydimethylsiloxane is 20%, the performance of the coating is the best. (The above breakdown energy level, dynamic friction coefficient, printing noise and print head pollution data are all between 0.11-0.15g / m 2 Measured within the coating weight range).
[0124] Example 7
[0125] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of catalyst dibutyltin dilaurate added is 0.08% of the total mass of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0126] Example 8
[0127] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of catalyst dibutyltin dilaurate added is 0.13% of the total mass of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0128] Example 9
[0129] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of catalyst dibutyltin dilaurate added is 0.05% of the total mass of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0130] Example 10
[0131] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the catalyst dibutyltin dilaurate added is 0.15% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0132] Embodiment 11
[0133] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of catalyst dibutyltin dilaurate added is 0.2% of the total mass of monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0134] Test Example 2
[0135] Effect of the addition amount of catalyst DBTDL on the stability of organosilicon-modified polyurethane-acrylate emulsion The thermal transfer carbon ribbons prepared in Example 1 and Examples 7 to 11 were tested for performance using organosilicon-modified polyurethane-acrylate back coating liquid.
[0136] The specific results are as follows:
[0137]
[0138] From the above results, it can be seen that the control of the molecular weight of the carbon-carbon double bond terminated organosilicon-modified polyurethane prepolymer of the present invention is the key to the success of the present invention. If the molecular weight of the prepolymer is too low, when the acrylic monomers (MMA and BA) are added for free radical polymerization, the reaction is violent, gelation is easy to occur, and it is difficult to control; if the molecular weight of the prepolymer is too high, the reaction rate is slow and the reaction time is long. The molecular weight can be controlled by changing the amount of catalyst DBTDL added.
[0139] As shown in the table above, when the addition amount of DBTDL is 0.05%, the molecular weight is too low, and gelation occurs after free radical polymerization of acrylate monomers; when the addition amount of DBTDL is 0.08%-0.13%, the reaction is normal; when the addition amount is ≥0.15%, there are many side reactions and the solution turns yellow. Therefore, the addition amount of catalyst DBTDL should be controlled at 0.08%-0.13%.
[0140] Embodiments 12 to 17
[0141] Examples 12 to 17 are the same as Example 1 except that the content of the raw materials for preparing the thermal transfer carbon ribbon back coating material is different from that in Example 1.
[0142]
[0143] Test Example 3
[0144] Since the finished ribbon needs to be able to withstand a certain temperature test to prevent sticking at high temperatures, it generally needs to meet a high temperature requirement of at least 50°C. (When the ambient temperature exceeds the Tg value of the polymer, the coating material becomes soft and easily migrates to the topcoat, resulting in sticking.)
[0145] The present application adjusts the ratio of the soft and hard segments of the acrylic ester monomer (i.e., the ratio of MMA and BA) to control the Tg of the synthetic polymer within a certain range (Example 1 and Examples 12 to 17) to meet the above requirements.
[0146] Furthermore, in this test example, the back coating liquids prepared in Example 1 and Examples 12 to 17 were prepared into thermal transfer carbon ribbons for performance testing.
[0147] Note: The thermal transfer carbon ribbon in this test example was prepared by referring to the preparation method of carbon ribbon 3 in application example 1 (back coating liquid concentration is 3.5%), that is, except for the selected silicone modified polyurethane-acrylate back coating liquid, the rest of the preparation method is the same as carbon ribbon 3 in application example 1.
[0148] The specific test results are as follows:
[0149]
[0150] As can be seen from the table above, as the proportion of monomer BA increases, the Tg of the synthetic polymer decreases, the thermal performance becomes worse and worse, and the sticking phenomenon occurs (the thermal performance is characterized by placing the finished carbon ribbon in an oven at a certain temperature for 20 hours, taking it out, cooling it to room temperature, and quickly pulling it apart to see if it sticks). Therefore, the proportion of monomer BA cannot be too high and should be controlled at 3~7%.
[0151] Embodiment 18
[0152] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the initiator added is 0.3% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0153] Embodiment 19
[0154] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the initiator added is 0.6% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0155] Embodiment 20
[0156] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the initiator added is 0.2% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0157] Embodiment 21
[0158] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the initiator added is 1% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0159] Embodiment 22
[0160] This embodiment is the same as Embodiment 1 except that in step (A), "the amount of the initiator added is 1.5% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer".
[0161] Test Example 4
[0162] The present application has verified through experiments that by adjusting the amount of initiator BPO added (Example 1 and Examples 18 to 22), the molecular weight of the synthetic polymer is controlled, thereby regulating the brittleness and toughness of the synthetic back coating, thereby improving the bonding performance between the back coating agent and the substrate film.
[0163] Furthermore, in this test example, the back coating liquids prepared in Example 1 and Examples 18 to 22 were prepared into thermal transfer carbon ribbons for performance testing.
[0164] Note: The thermal transfer carbon ribbon in this test example was prepared by referring to the preparation method of carbon ribbon 3 in application example 1 (back coating liquid concentration is 3.5%), that is, except for the selected silicone modified polyurethane-acrylate back coating liquid, the rest of the preparation method is the same as carbon ribbon 3 in application example 1.
[0165] The specific test results are as follows:
[0166]
[0167] From the experimental results in the above table, it can be seen that when the addition amount of the initiator BPO is 0.3~0.6% and the molecular weight of the synthetic polymer is controlled at 50000-80000 g / mol, the performance of the back coating is better; and when the addition amount of BPO is not in the range of 0.3~0.6%, it is easy to cause print head contamination and the printing noise is relatively large.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a thermal transfer carbon ribbon back coating material, characterized in that: The material is a silicone-modified polyurethane-acrylate copolymer emulsion; The preparation method comprises: (A) in the presence of a catalyst, stirring and refluxing toluene diisocyanate and polytetramethylene ether diol to obtain a polyurethane prepolymer; (B) adding hydroxy-terminated polydimethylsiloxane dropwise to the polyurethane prepolymer for stirring and reflux reaction to obtain an organosilicon-modified polyurethane prepolymer, and then adding hydroxyethyl methacrylate for end-capping to obtain an organosilicon-modified polyurethane prepolymer end-capped with a carbon-carbon double bond; (C) adding an acrylate monomer and an initiator to a carbon-carbon double bond terminated organosilicon-modified polyurethane prepolymer for stirring and refluxing to obtain an organosilicon-modified polyurethane-acrylate copolymer emulsion; The organosilicon-modified polyurethane-acrylate copolymer comprises the following monomers, calculated by percentage of the total mass of the prepared monomers: 20-25% of polytetramethylene ether glycol, 10-16% of toluene diisocyanate, 14-25% of terminal hydroxyl polydimethylsiloxane, 3-6% of hydroxyethyl methacrylate, 35-40% of methyl methacrylate, and 3-7% of butyl acrylate; The catalyst in step (A) is dibutyltin dilaurate, and the amount of the catalyst added in step (A) is 0.08-0.13% of the total mass of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer; The amount of the initiator added in the step (C) is 0.3-0.6% of the total weight of the monomers for preparing the organosilicon-modified polyurethane-acrylate copolymer.
2. The method for preparing the thermal transfer carbon ribbon back coating material according to claim 1, characterized in that: In the step (C), the initiator is one of benzoyl peroxide and azobisisobutyronitrile.
3. The method for preparing the thermal transfer carbon ribbon back coating material according to claim 1, characterized in that: The polytetrahydrofuran ether diol in the step (A) is polytetrahydrofuran ether diol after vacuum drying and dehydration, and the temperature of the vacuum drying and dehydration is 110° C.; And / or, the terminal hydroxyl polydimethylsiloxane in the step (B) is the terminal hydroxyl polydimethylsiloxane after vacuum drying and dehydration, and the temperature of the vacuum drying and dehydration is 110°C.
4. The method for preparing the thermal transfer carbon ribbon back coating material according to claim 1, characterized in that: The following monomers are included, based on the total monomer percentage for preparing the organosilicon-modified polyurethane-acrylate copolymer: 21% of polytetramethylene ether glycol, 12% of toluene diisocyanate, 20% of terminal hydroxyl polydimethylsiloxane, 5% of hydroxyethyl methacrylate, 38% of methyl methacrylate, and 4% of butyl acrylate.
5. A thermal transfer carbon ribbon back coating material, characterized in that: The thermal transfer carbon ribbon back coating material is mainly prepared by the preparation method of the thermal transfer carbon ribbon back coating material according to any one of claims 1 to 4.
6. A back coating liquid for thermal transfer carbon ribbon, characterized in that: The back coating liquid is mainly obtained by diluting the thermal transfer carbon ribbon back coating material according to claim 5 with a solvent; The solvent is a mixed solvent, and the mixed solvent includes at least two of toluene, butanone and methanol.
7. The back coating liquid for thermal transfer carbon ribbon according to claim 6, characterized in that: The content of the thermal transfer carbon ribbon back coating material in the back coating liquid is 15-25wt%.
8. The back coating liquid for thermal transfer carbon ribbon according to claim 7, characterized in that: The content of the thermal transfer carbon ribbon back coating material in the back coating liquid is 20wt%.
Citation Information
Patent Citations
High-silicon-content organic silicon-polyurethane-acrylate composite coating agent and preparation method thereof
CN102585650A